Intervensi Teknik Restrukturisasi Kognitif pada Korban Cyber Grooming: Studi Kasus - Magfira, Shinta; Harum, Akhmad; Fitriana, Fitriana (Universitas Sebelas Maret, 2025)
This study aims to examine the effectiveness of cognitive restructuring techniques in helping a student recover from the psychological impact of cyber grooming. The intervention focuses on reducing cognitive distortions, restoring emotional stability, and strengthening the student's confidence after experiencing online manipulation. This Research uses a qualitative case study design. The subject is a male student who exhibited fear, shame, and negative assumptions about his reputation after the incident. Data were collected through in-depth interviews, observation, and documentation, then analyzed using a thematic approach. The results show that the student experienced several cognitive distortions, including self-blame and exaggerated fear of social judgment. Through six counseling sessions using Cognitive Behavioral Therapy, the student identified irrational thoughts, challenged them, and replaced them with more realistic and balanced thinking. Improvements were also seen in emotional regulation, social interaction, and motivation to return to normal activities. The study concludes that cognitive restructuring is effective for helping victims of cyber grooming manage distorted thoughts and reduce emotional distress. Future research is encouraged to explore similar interventions with larger samples, compare different counseling approaches, and examine long-term outcomes after treatment.